Exploring Flood and Erosion Risk Indices for Optimal Solar PV Site Selection and Assessing the Influence of Topographic Resolution - Yilmaz, Kutay; Dincer, Ali Ersin; Ayhan, Elif N. (Pergamon-Elsevier Science Ltd, 2023)
This study explores the suitability of Mentes,e Region in Turkiye for the installation of solar PV farms, given the significant increase in energy demand in the country and the need to reduce reliance on fossil fuels. The Analytical Hierarchy Process (AHP) method, which has been widely used in previous studies, is employed to identify the most influential criteria for site selection, including environmental, economic, and social factors. However, this study introduces two new factors, flood hazard and erosion indices, to the analysis, which are crucial in areas susceptible to these hazards. The results show that approximately 7.5% of the study surface area is suitable for solar PV production. The study reveals that flood hazard and erosion indices have an effect on the suitable sites despite their relatively lower weights in the AHP. In addition, the study illustrates that site selection can be carried out using topographic data of lower resolution, as long as the data is resampled to match the resolution of land use data. The study is novel in its integration of flood and erosion risk indices in the decision process and its investigation of the influence of topographic resolution on site selection for solar PV panels.
Yilmaz, Kutay/0000-0001-5529-9239; Ayhan, Elif Nagihan/0000-0003-1393-3494; Dincer, Ali Ersin/0000-0002-4662-894X;
Keywords: Renewable Energy; Solar PV Site Selection; Analytical Hierarchy Process (AHP); Multi-Criteria Decision-Making (MCDM); Flood; Erosion